Kajian Konseptual Konsumsi dan Tabungan dalam Perspektif Ekonomi Konvensional dan Islam - Thania Ramadhani; Nova Sulistiani Safitri; Reza Wardana; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Consumption and saving play an important role in shaping household economic behavior and overall economic stability. This study aims to analyze the concept of consumption and saving from the perspectives of conventional economics and Islamic economics, as well as to examine their relevance to current economic conditions in Indonesia. This research applies a qualitative descriptive method using a literature review approach by analyzing books, scientific journals, and official publications related to consumption, saving, and Islamic economic principles. The findings indicate that conventional economics views consumption as being primarily determined by disposable income, while saving represents the remaining portion of income after consumption. In contrast, Islamic economics emphasizes ethical consumption based on halal principles, moderation, and social responsibility, and views saving as a means to achieve economic balance and social welfare through mechanisms such as zakat and charity. The study highlights that integrating Islamic values can support more sustainable and responsible financial behavior.